Movement sonification: Intermodal transformation of movement data to enhance motor learning - Effenberg, A. O.; Hwang, T.-H. (Sports technology. Fields of application, sports equipment and materials for sport, 2024)
Contrasted to `visualization`, the term `sonification` refers to an acoustic transformation of data into sound. Human movement sonification based on kinematic and dynamic data offers multifaceted innovative applications in sports concerning enhancement in motor-perception, motor control and motor learning, mainly referring to closed skills. With the transformation of originally visual information into the auditory domain the specific power of the auditory and musical perceptual system will be integrated comprehensively into behavioral regulation. Particularly, real-time movement sonification can get effectively in novel ways, if configured convergently to visual or kinesthetic information: It has been shown that, seamlessly integrated with information from other perceptual modalities, it modulates and enhances perceptual-, control-, and even learning-processes—not only individually, but also interpersonally.